Effect of Impeller Inlet Geometry on Cavitation Performance of Centrifugal Pumps Based on Radial Basis Function - Shuwei Zhang; Renhui Zhang; Sidai Zhang; Junhu Yang (International Journal of Rotating Machinery)
Aiming at the cavitation problem, the blade leading edge shape has been changed to analyze its impact on the cavitation performance for centrifugal pumps. And the response model has been established based on the Radial Basis Function. The calculation case results show that the leading edge extending forward along the shroud can improve the inlet flow condition and cavitation performance. But the cavitation performance has been reduced immensely when the leading edge extends backward along the shroud. Along with the leading edge which extends forward along the hub, the cavitation performance increases at first and then decreases. A better cavitation performance for centrifugal pumps has lower load of blade inlet and higher pressure of blade suction side. The pressure pulsation is affected by the vortex out of the impeller and the falling-off and collapsing of the cavitation bubbles. The lower the pressure pulsation for blade passing frequency and the second harmonics of the samples is, the better the cavitation performance is. A relatively accurate response model based on the Radial Basis Function has been established to predict the effect of the shape of blade leading edge on the cavitation performance of centrifugal pumps.